At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

What is the solution [tex]\((a, b)\)[/tex] to this system of linear equations?
[tex]\[
\begin{array}{l}
3a + 6b = 45 \\
2a - 2b = -12
\end{array}
\][/tex]

A. [tex]\((-27, 6)\)[/tex]
B. [tex]\((-1, 7)\)[/tex]
C. [tex]\((1, 7)\)[/tex]
D. [tex]\((27, -6)\)[/tex]


Sagot :

Let's solve the system of linear equations to find the values of [tex]\( a \)[/tex] and [tex]\( b \)[/tex]. The given system is:

[tex]\[ \begin{cases} 3a + 6b = 45 \\ 2a - 2b = -12 \end{cases} \][/tex]

Step 1: Simplify the equations if possible

Let's look at the second equation:

[tex]\[ 2a - 2b = -12 \][/tex]

We can divide every term by 2 to simplify:

[tex]\[ a - b = -6 \implies a = b - 6 \][/tex]

Now we have:

[tex]\[ 3a + 6b = 45 \][/tex]

Step 2: Substitute [tex]\( a \)[/tex] in the first equation

From the simplified second equation [tex]\( a = b - 6 \)[/tex], we substitute [tex]\( a \)[/tex] into the first equation:

[tex]\[ 3(b - 6) + 6b = 45 \][/tex]

Expand and simplify:

[tex]\[ 3b - 18 + 6b = 45 \][/tex]

Combine like terms:

[tex]\[ 9b - 18 = 45 \][/tex]

Add 18 to both sides:

[tex]\[ 9b = 63 \][/tex]

Divide by 9:

[tex]\[ b = 7 \][/tex]

Step 3: Find [tex]\( a \)[/tex]

Now that we have [tex]\( b \)[/tex], substitute [tex]\( b \)[/tex] back into [tex]\( a = b - 6 \)[/tex]:

[tex]\[ a = 7 - 6 = 1 \][/tex]

Thus, the solution to the system is [tex]\( (a, b) = (1, 7) \)[/tex].

Step 4: Verify the solution

To ensure that our solution is correct, substitute [tex]\( a = 1 \)[/tex] and [tex]\( b = 7 \)[/tex] back into the original equations:

First equation:

[tex]\[ 3(1) + 6(7) = 3 + 42 = 45 \quad \text{(Correct)} \][/tex]

Second equation:

[tex]\[ 2(1) - 2(7) = 2 - 14 = -12 \quad \text{(Correct)} \][/tex]

So, the solution is indeed correct.

The correct solution [tex]\( (a, b) \)[/tex] for the given system of linear equations is:

[tex]\[ (1, 7) \][/tex]

Among the given choices:
- [tex]\((-27, 6)\)[/tex]
- [tex]\((-1, 7)\)[/tex]
- [tex]\((1, 7)\)[/tex]
- [tex]\((27, -6)\)[/tex]

The solution is [tex]\( (1, 7) \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.